Serum-Derived Exosomal miR-140-5p as a Promising Biomarker for Differential Diagnosis of Anti-NMDAR Encephalitis With Viral Encephalitis - Liu, Xiaofeng; Fan, Kengna; Lin, Qingwen; Tang, Minjie; Wang, Qi; Huang, Er; Zhang, Weiqing; Chen, Tianbin; Ou, Qishui (Frontiers in Immunology, 2022)
Background: Anti-N-methyl-D-aspartate receptor(anti-NMDAR) encephalitis is the most common type of autoimmune encephalitis. Early recognition and treatment, especially distinguishing from viral encephalitis (VE) in the early stages, are crucial for the outcomes of patients with anti-NMDAR encephalitis. Compared with plasma miRNAs, exosomal miRNAs are more abundant and not easy to degrade. Moreover, exosomes can pass through the blood-brain barrier. This study aimed to explore the clinical value of serum exosomal miRNAs in the differential diagnosis of anti-NMDAR encephalitis with VE. Method: A total of 30 patients with anti-NMDAR encephalitis, 30 patients with VE, and 30 cases of control patients hospitalized in the same period were collected. Firstly, the serum exosomes were isolated and identified by transmission electron microscope (TEM), nanoparticle-tracking analyzer (NTA) and Western Blot (WB). Then the expression levels of let-7b, miR-140-5p from serum exosomes were detected by real-time quantitative PCR (qPCR). At the same time, we also detected complement 3 (C3), complement 4 (C4) and high sensitivity CRP (hs-CRP) expression levels in three groups. Finally, we analyzed the difference and diagnostic value of the test results. Results: Isolated particles showed identical characteristics to the exosomes through TEM, NTA, and WB analysis. Compared with the VE group and control group, the expression of miR-140-5p was significantly upregulated in serum exosomes of the NMDAR group. Contrary, the serum C3 in the NMDAR group was significantly lower than the other two groups. ROC-curve analysis showed the AUC of serum exosomal miR-140-5p and serum C3 was 0.748 (76.67% sensitivity and 73.33% specificity) and 0.724 (76.67% sensitivity and 60% specificity) to distinguish anti-NMDAR encephalitis from VE, respectively. The AUC of serum exosomal miR-140-5p combined with serum C3 was 0.811, the sensitivity was 70.00%, and the specificity was 86.67%. Conclusion: Serum exosomal miR-140-5p combined with serum C3 would be a promising marker in the differential diagnosis of anti-NMDAR encephalitis with VE.